2013
DOI: 10.1097/mat.0b013e3182976939
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cerebral Microcirculation During Pulsatile and Nonpulsatile Selective Cerebral Perfusion

Abstract: Currently, nonpulsatile selective cerebral perfusion for cerebroprotection against thoracic aortic aneurysm is used in clinical settings. We performed synchrotron radiation microangiography to determine the effects on selective cerebral perfusion modulation by pulsatile flow. We established cerebral perfusion at normothermia and severe hypothermia in anesthetized rats, during which cerebral angiography was performed. NG-nitro-L-arginine-methyl ester hydrochloride (L-NAME) was administered to determine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Moreover, our results demonstrated that pulsatile ECMO produces methemoglobin levels within the normal range, compared with nonpulsatile ECMO. Nitric oxide secretion from the endothelium is stimulated by the mechanical shear stress of pulsatile flow acting on vessel endothelium (25). This indicates that pulsatile flow produces more nitric oxide than nonpulsatile flow (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results demonstrated that pulsatile ECMO produces methemoglobin levels within the normal range, compared with nonpulsatile ECMO. Nitric oxide secretion from the endothelium is stimulated by the mechanical shear stress of pulsatile flow acting on vessel endothelium (25). This indicates that pulsatile flow produces more nitric oxide than nonpulsatile flow (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide secretion causes systemic vasodilation by diffusing into vascular smooth muscle cells (19,21). Nitric oxide secretion from the endothelium is stimulated by the mechanical shear stress of pulsatile flow acting on vessel endothelium (25). For this reason, pulsatile blood flow may reduce systemic vascular resistances and maintain better circulation in microvessels by increasing nitric oxide secretion.…”
Section: Discussionmentioning
confidence: 99%
“…; Inamori et al . ). Importantly, the authors also reported, ‘pulsatility resulted in a reduction in the prevalence of pathologic hyper‐dynamically perfused vessels’ (O'Neil et al .…”
Section: Schematic Of the Device Location And Components And Typical mentioning
confidence: 97%
“…In any case, it is important to consider cardiac output in relation to the local peripheral vasodilatation and vasoconstriction. Studies examining the effects of pulsatile cardiopulmonary bypass reported that the number of perfused vessels in the microcirculation was increased compared with a continuous-flow circulation (O'Neil et al 2012;Inamori et al 2013). Importantly, the authors also reported, 'pulsatility resulted in a reduction in the prevalence of pathologic hyper-dynamically perfused vessels' (O'Neil et al 2012).…”
Section: Additional Considerationsmentioning
confidence: 99%
“…For example, Recchia et al and Kassab et al demonstrated that PF increases in vivo coronary flow, in part by triggering NO release. Inamori et al showed the efficacy of PF for enhancing cerebral microvessel perfusion and the effect of NO production on this process. Lazaro et al, Opatrny et al, and von Horn et al observed that PF preserved kidney perfusion during organ storage and kidney function after autotransplantation.…”
Section: Introductionmentioning
confidence: 99%